Location Quotient Analysis in Determining the Economic Leading Sector of West Sulawesi Province- Indonesia - Zulkifli; Dahlia (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to determine the leading sectors in the Province of West Sulawesi. It was quantitative descriptive research. The primary data was statistical data while the secondary data was a library data which was taken from West Sulawesi Province GRDP year 2010-2019. The data was analysed using the Location Quotient (LQ) analysis. The results showed that the leading sectors in the province of West Sulawesi Indonesia were (1) the agriculture sector, (2) the financial sector, (3) the company rental & services, and (4) the transportation and communication sector. The findings are essential to be used as a recommendation for the local government in raising the economic growth of West Sulawesi Province people in Indonesia.